Características histopatológicas e imunohistoquímicas dos carcinomas de tireoide em cães - Soares, Luciana Maria Curtio (2019)
Thyroid carcinomas are a common form of endocrine neoplasia in dogs. In the present study, we combined histopathology with immunohistochemical staining for oestrogen receptor alpha (ERα), Cox-2, and Ki-67 in canine thyroid carcinoma. Biopsy reports of the Veterinary Analysis Laboratory - VETPAT, Campinas, São Paulo were reviewed, including data from 20142016. Data regarding age, sex, and breed of the affected dogs, and histomorphological diagnosis of the tumours including histological patterns (presence or absence of vascular, capsular, and adjacent invasion, haemorrhage, necrosis, and cell pleomorphism) were selected and evaluated. Fortyeight thyroid carcinomas were diagnosed throughout the study period. Of the affected dogs, The sex ratio was similar; most of the animals (16.70%) were mixed breed (SRD), followed by purebred Beagle (12.50%) and Boxer (10.42%). A total of 68.75% of the dogs were older. Thyroglobulin and calcitonin immunohistochemistry (IHC) could distinguish between thyroid tumours with a follicular and medullary (C-cell) origin, respectively. IHC-based diagnosis showed that 42 (87.50%) neoplasms were follicular cell carcinoma and in these cases, the follicular-compact pattern was the most frequent (n = 20/42; 47.62%) and 6/42 (12.50%) were medullary cell carcinoma. Both medullary and follicular carcinomas expressed Ki-67 and Cox2. No differences were observed between medullary and follicular carcinomas and Ki-67 (p = 0.34) and Cox-2 (p = 0.9523) markers. A total of 4.17% (n = 2/48) of thyroid carcinomas showed positive nuclear labelling for ERα. In summary, oestrogen does not directly participate in canine thyroid neoplasia.